Resveratrol enhances post-injury muscle regeneration by regulating antioxidant and mitochondrial biogenesis - Xiaoli Qin; Wenjing Niu; Kai Zhao; Yawen Luo; Wenfang Wang; Yang He; Fuyu Yang; Binghai Cao; Min Du; Huawei Su (Current Research in Food Science)
Resveratrol (RES), a natural polyphenolic compound, has shown promise in enhancing skeletal muscle regeneration and metabolic function. This study aims to explore the impact of RES on muscle regeneration after injury through the regulation of antioxidant capacity and mitochondrial biogenesis. RES treatment significantly increased the ratio of tibialis anterior muscle mass to body weight, alongside reduced fasting glucose levels. Following cardiotoxin-induced injury, RES treatment improved muscle regeneration, characterized by greater formation of new fibers and better structural repair compared to the control. Notably, gene expression analyses demonstrated that RES-treated mice exhibited elevated levels of myogenic markers, such as paired box 7 (Pax7), myogenic factor 5 (Myf5), myoblast determination protein (MyoD), and Myogenin (MyoG). Concurrently, yes-associated protein (YAP) increased, underscoring its role in regulating satellite cell activity. Transcriptomic analysis identified enriched pathways related to muscle regeneration and mitochondrial biogenesis, with increased expression of mitochondrial transcription factors and higher mitochondrial DNA content in RES-treated mice. Furthermore, RES enhanced antioxidant capacity via the Kelch-like ECH-associated protein 1 (KEAP-1)/nuclear factor erythroid 2-related factor 2 (NRF2)/heme oxygenase-1 (HO-1) signaling pathway, as indicated by elevated activities of total antioxidant capacity, Glutathione peroxidase (GSH-PX), and superoxidase dismutase (SOD). Collectively, these findings suggest that RES not only promotes muscle regeneration but also supports mitochondrial function and antioxidant defenses, positioning it as a food-derived pharmaceutical for targeting muscle repair after injury.